Chemichal Quality and Microbiology of Village Chicken Meat with Infusation Treatmnet of Soursop Leaf (Annona Muricata Lin) - Burhanudin Shodiq; Engkus Ainul Yakin; Ludfia Windyasmara (Bantara Journal of Animal Science, 2021)
Chicken meat is one of the foodstuffs that have high nutritional value because it contains carbohydrates, proteins, fats, minerals and other substances that are beneficial to the body. Chicken meat is very high risk in terms of bacterial contamination, this study aims to determine the treatment of soaking native chicken meat in soursop leaf infusion on chemical and microbiological quality. This method uses a completely randomized design (CRD). The data obtained were analyzed statistically using Analysis Of Variance (ANOVA). If there is a significant significant difference between treatments, the test is continued with Duncan Multiple Range (DMRT). Parameters observed in this study include phenol test, total plate count test, and bacterial inhibition zone test. The results showed the chemical and microbiological quality of free-range chicken meat by soaking soursop leaf infusion for one hour and different storage times, namely the difference was not significant (P<0.1) in the phenol test, the difference was very significant (P<0.01) in the total test. plate count, and non-significant (P>0.1) in the bacterial inhibition zone test. The results showed a very significant difference in the total plate count test due to contamination during research or storage.